A Review on Smart Plant Monitoring System - Ashwini Patil; Ashwini Mali (Journal of Electronic Design Engineering, 2017)
Environmental factor monitoring is very important since the last few decades. It has become very significant to monitor the agricultural environments for various factors such as temperature, moisture, humidity along with other factors can be of more significance. Automated plant monitoring system consists of a feedback control system that employs monitoring of environmental parameters such soil moisture, temperature and humidity are measured which plays an important role in overall development of the crop and good yield. Conservation of water and other resource can be achieved by optimizing these parameters. A traditional approach for measuring these factors in an agricultural environment meant individuals manually taking measurements and checking them at various times. In this paper, plant monitoring systems using wireless protocols used by different researchers for betterment of agricultural yield with best possible technologies is reviewed. The paper also reviews the various sensors available to monitor above environmental parameters and focuses on smart plant monitoring to suite such types of end application.